Utilization of gram and oat flour cookies for diabetes - Noor-ul-Ain; Syed iqtadar Ali Rizvi; Samina Arshad (Medical Journal of South Punjab, 2025)
Objective: To evaluate the nutritional, glycemic, and sensory attributes of cookies formulated with gram (chickpea) and oat flour for potential dietary management in individuals with type 2 diabetes mellitus. Methodology: This was experimental, randomized controlled trial (RCT). A total of 60 participants (aged 35–65) with diagnosed type 2 diabetes were enrolled. Patients were divided into two grouos. Group A (Intervention Group): Received 50g/day of gram and oat flour cookies. Group B (Control Group): Received 50g/day of standard refined wheat flour cookies. Results: Group A’s postprandial blood glucose fell from 198 ± 15 to 160 ± 14 mg/dL. Group B’s decreased from 196 ± 14 to 182 ± 15 mg/dL. These were also significant (p < 0.01). HbA1c in Group A declined from 7.8 ± 0.4% to 6.9 ± 0.3%. In Group B, it dropped from 7.7 ± 0.5% to 7.5 ± 0.4% (p < 0.05). Group A’s BMI reduced from 27.2 ± 1.5 to 26.5 ± 1.4 kg/m². Group B’s changed slightly from 27.1 ± 1.6 to 27.0 ± 1.5 kg/m². These were not statistically significant. The Intervention Cookie scored 8.1 (appearance), 7.9 (taste), 7.5 (texture), and 8.0 (overall). The Control Cookie scored slightly higher: 8.5, 8.4, 8.0, and 8.3, respectively. Conclusion: Cookies made from gram and oat flour showed significantly better glycemic outcomes compared to conventional cookies, with favorable sensory properties. The combination of high fiber and low GI ingredients may serve as a potential dietary adjunct for individuals with type 2 diabetes.